PERAN MISIONARIS DALAM MEMBANGUN KULTUER PENDIDIKAN KATOLIK DI MANGGARAI RAYA PASCA KEMERDEKAAN (1955 DAN 1983) - Nurut, Avika Triningsi (KARMAWIBANGGA: Historical Studies Journal, 2021)
This study aims to determine the role of missionaries in building a Catholic Education Culture in Manggarai Raya Post Independence (1995 and 1983). The method used is qualitative descriptive. Data in this study were collected throught the observation, interview dan documentation stage. The results of the study concluded tha the arrival of missionaries such as the Pius XII Kisol seminary and St. Klaus Junior hihg School. Many schools were built not only solely for the benefit of the Catholic church but also as a form of their concern for the civilization of society in Manggarai Raya.